Pengaruh Trunk Control Activity Terhadap Tingkat Kemandirian Aktivitas Kehidupan Sehari-Hari (Activity Of Daily Living) Pasien Pasca Stroke - Mudatsir Syatibi; Hendri Kurniawan; Rita Untari (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Trunk Control, Activity Of Daily Living. The purpose of this study was to determine the effect of trunk control activity on the level of post-stroke patients independence in performing activities of daily life (activity of daily living). The study design was performed according to quasi experimental design with a control group pretest-posttest design. The study population was patients with post-stroke conditions that obtain in Clinical intervention Sasana Husada Group. Sampling using quota sampling with a sample size of 30 people. Data analysis using independent t-test using SPSS version 11.5. Results of analysis using independent t-test showed the value of F = 0.611 (equal variances assumed), t = 3.654 and p-value = 0.001. Trunk control activity significantly affect the level of independence of daily life activity (activity of daily living) post-stroke patients.